Association of tumor location with anxiety and depression in childhood brain cancer survivors: a systematic review and meta-analysis - Márton Szabados; Erika Kolumbán; Gergely Agócs; Szilvia Kiss-Dala; Marie Anne Engh; Márk Hernádfői; Kata Takács; Eszter Tuboly; Andrea Párniczky; Péter Hegyi; Miklós Garami (BMC, 2023)
Abstract Objective This study aimed to evaluate the association between the location (supratentorial or infratentorial) of brain tumors and the development of depression and anxiety in childhood cancer survivors. Understanding the risk factors for the development of depression and anxiety disordersin these patients is crucial for early diagnosis and successful treatment. Methods The meta-analysis included articles that listed patients diagnosed with an intracranial tumor before the age of 18 years, provided the location of the tumor, had exact data on the prevalence of anxiety and depression, or measured these disorders using different assessment tools. The search was conducted in five different databases (MEDLINE, Embase, Web of Science, Scopus, and Cochrane Library). Risk of bias was assessed using QUIPS-2. Outcome measures used were prevalences and standardized means. Results The analysis included 42 eligible articles with a total number of 1071 patients. Relevant articles were cohort studies, cross-sectional studies, and case series. Based on the available data infratentorial brain tumor survivors had significantly higher scores on various assessment tools measuring anxiety (MRAW (raw mean scores): 36.24 [CI (confidence interval): 28.81-43.67]; versus MRAW: 23.21 (CI 0.91-45.51); p = 0.02, and depression (MRAW: 27.57 (CI 14.35-40.78) versus MRAW: 13.84 (CI 11.43-16.26); p < 0.01. Conclusion Childhood infratentorial cancer survivors have more impairments in terms of depression and anxiety; these children and adults should be monitored more frequently and may require closer follow-up on their mental health. The main limitation of our study originates from the lack of data on follow-up times used by different studies.